Створення ІКС «Чиста Україна» для моніторингу забруднення територій - Посторонко, Н. М.; Трушаков, Д. В.; Козловський, О. А.; Федотова, М. О.; Postoronko, N.; Trushakov, D.; Kozlovskyi, О.; Fedotova, M. (ЦНТУ, 2022)
Статтю присвячено створенню спеціалізованої інформаційно-комунікаційної системи (ІКС), яка б допомогла виявляти забруднення вулиць, факти вандалізму та швидко їх усувати. Основною метою дослідження є автоматизація процесу сповіщення та комунікації установ, що займаються прибиранням території вулиць міст та селищ України. Завданням дослідження є створення макету програмного забезпечення інформаційно-комунікаційної системи – макету веб ресурсу та макету мобільного додатку «Чиста Україна». Це дозволить установам, що займаються прибиранням території в режимі online виявляти забруднення вулиць та факти вандалізму шляхом комунікації з населенням та швидко їх усувати. Шляхом проведеного аналізу існуючих інформаційно-комунікаційних систем визначено найбільш оптимальне рішення - побудовано алгоритм роботи інформаційно-комунікаційної системи “Чиста Україна”. В результаті проведеного дослідження було створено макет веб ресурсу інформаційно-комунікаційної системи та макет мобільного додатку «Чиста Україна», що дозволяють виявляти забруднення вулиць та факти вандалізму шляхом комунікації установ з населенням та швидко їх усувати. Завдяки цьому можна значно скоротити час на виявлення забруднень та збільшити ефективність праці установ, що займаються прибиранням територій у містах та селищах України. The article is devoted to the creation of a specialized information and communication system that would help detect street pollution, vandalism and eliminate them quickly. The main purpose of the study is to automate the process of notification and communication of institutions engaged in cleaning the streets of cities and towns of Ukraine. The task of the research is to create a layout of the software of the information and communication system - the layout of the web resource and the layout of the mobile application "Clean Ukraine". This will allow online clean-up agencies to detect street pollution and vandalism by communicating with the public and removing them quickly. By analyzing the existing information and communication systems, the most optimal solution was determined - the algorithm of the information and communication system "Clean Ukraine" was built. As a result of the study, a layout of the web resource of the information and communication system and a layout of the mobile application "Clean Ukraine" were created, which allows to detect street pollution and vandalism by communicating with the population and quickly eliminate them. An interactive layout of the Clean Ukraine mobile application was created on the Figma platform. The algorithm of this information and communication system is as follows. If the applicant person has discovered street pollution or vandalism, this fact must be recorded in a photo or video. You need to go to the created information and communication mobile application or web resource and fill out the form of notification of pollution or vandalism and attach a photo or video file. Employees of the relevant specialized institution read the message. If the message is meaningful and detailed, the staff of the institution passes it to the service, which cleans the area and eliminates the consequences of pollution. Employees of the specialized institution inform the applicant about the work performed. This can significantly reduce the time to detect contaminants and increase the efficiency of institutions involved in cleaning up the area. Thanks to the introduction of the presented information and communication system, it will be possible to improve the quality of cleaning the streets of cities and towns of Ukraine. Also, this system will create new jobs for which people do not need special education. Many of this work will be filled by people who will work remotely checking user requests.
Creation of an Information and Communication System «Clean Ukraine» for Monitoring Territory Pollution
Keywords: інформаційно-комунікаційна система; платформа Figma; WEB сайт; мобільний додаток; забруднення вулиць та територій; комунікація з населенням; information and communication system; Figma platform; WEB site; mobile application; pollution of streets and territories; communication with the population